2018
DOI: 10.1021/acs.est.8b02215
|View full text |Cite
|
Sign up to set email alerts
|

Urine Metabolic Signatures of Multiple Environmental Pollutants in Pregnant Women: An Exposome Approach

Abstract: 31Exposure to environmental pollutants, particularly during pregnancy, can have adverse consequences 32 on child development but little is known about the effects of pollutant mixtures on endogenous 33 metabolism in pregnant women. We aimed to identify urinary metabolic signatures associated with 34 low level exposure to multiple environmental pollutants in pregnant women from the INMA (INfancia y 35 Medio Ambiente) birth cohort (Spain, N=750). 36 35 chemical exposures were quantified in first trimester blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 69 publications
1
49
0
1
Order By: Relevance
“…Mothers sometimes breathe dust in rooms with wallpaper or flooring containing EDCs or touch products made with BPA. A number of studies have revealed that some EDCs can be detected in the serum, amniotic fluid, breast milk, and urine of pregnant women [15,16]. Some of these may accumulate in placental tissues, and impair placental function, including plasticizers, organochlorine pesticides, personal care products, or naturally occurring EDCs found in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers sometimes breathe dust in rooms with wallpaper or flooring containing EDCs or touch products made with BPA. A number of studies have revealed that some EDCs can be detected in the serum, amniotic fluid, breast milk, and urine of pregnant women [15,16]. Some of these may accumulate in placental tissues, and impair placental function, including plasticizers, organochlorine pesticides, personal care products, or naturally occurring EDCs found in plants.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study applied a O2PLS approach in pregnant women from the Spanish INMA birth cohort to assess the association between multiple chemical exposures (> 30) and urine 1 H nuclear magnetic resonance metabolomics (> 60). This allowed the identification of common route of exposures such as fish intake and oxidative stress of chemical exposures with known detrimental health effects [81]. When multiple omics profiles are available in the same individuals, cross-omics analyses investigate how exposure and/or outcome-related signals found at one molecular level correlate to those found at another level, gaining insight into the molecular cascades related to that specific exposure and/ or outcome [82].…”
Section: Incorporating Omics Into Exposome Researchmentioning
confidence: 99%
“…quantification of environmental chemicals), 2) metabolic imprints of exposure or exposure-metabolite associations (e.g. total arsenic in urine associates with the gut bacteria metabolite TMAO in pregnant women [4]), 3) the biological impact of exposures (e.g. acetylcholinesterase activity is a biomarker of organophosphate exposure) and 4) processes that reflect wear and tear in the individual (e.g.…”
Section: Analysing the Exposomementioning
confidence: 99%